Association of monocyte/high-density lipoprotein cholesterol ratio with periodontitis: a cross-sectional study based on the NHANES database - HU Zhiqiang; ZHANG Qi; LI Xinpeng; CUI Yuchen; YUAN Jiamin; ZHU Xianchun (口腔疾病防治)
Objective To investigate the association between monocyte to high-density lipoprotein cholesterol ratio (MHR) and periodontitis and to provide new epidemiologic evidence on the factors affecting periodontitis. Methods Data on MHR, periodontitis, and other covariates were selected from the NHANES(National Health and Nutrition Examination) database for 3 cycles of subjects in 2009-2010, 2011-2012, and 2013-2014, and a total of 8 456 study subjects were included. The study participants were grouped according to the prevalence of periodontitis (presence or absence), and three regression models (unadjusted covariates, partially adjusted covariates, and fully adjusted covariates) were constructed to analyze the relationship between MHR and periodontitis by using a weighted logistic regression method with stepwise adjustment for confounders. MHR was divided into four groups from Q1 to Q4 according to quartiles from small to large for weighted trend analysis, and the nonlinear relationship between MHR (continuous) and periodontitis was analyzed using a restricted cubic spline with subgroup analysis and sensitivity analysis. Results All three logistic regression models showed a positive association between MHR and periodontitis (OR = 2.92, 95%CI: 2.14-3.99, P<0.001 (not adjusted); OR = 1.97, 95%CI: 1.39-2.78, P<0.001 (partially adjusted); OR = 1.62, 95%CI: 1.10-2.39, P = 0.017 (fully adjusted)). Trend analysis showed a significantly higher risk of developing periodontitis in the Q4 group compared with the Q1 group in both single (OR = 1.92, 95% CI: 1.58-2.33, P<0.001) and multifactorial analyses (OR = 1.30, 95% CI: 1.03-1.64, P = 0.029). Restricted cubic spline results did not support a nonlinear relationship between MHR and periodontitis (P for nonlinear>0.05), subgroup analysis showed no significant interaction between the covariates and MHR (P>0.05), and sensitivity analysis also showed a positive correlation between MHR and periodontitis (OR = 1.67, 95%CI: 1.31-2.14, P<0.001). Conclusion MHR is positively associated with the risk of developing periodontitis.